1997
DOI: 10.1103/physrevb.55.r14717
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hysteresis anomalies in ferritin

Abstract: Ferritin, an antiferromagnetic nanoparticle with a net magnetic moment, exhibits some unusual magnetic behavior. Above its blocking temperature, T B Ϸ12 K, the magnetization can be fit with the Langevin function only by including an additional linear term. The saturation moment decreases linearly with increasing temperature, and suggests an ordering temperature of about 460 K. Below T B , both zero-field-cooled and fieldcooled hysteresis loops exhibit large coercivity (ϳ1800 Oe͒ and irreversibility in the loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
224
2
13

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(281 citation statements)
references
References 9 publications
35
224
2
13
Order By: Relevance
“…Still, the dependence of the magnetization on particle size and temperature has shown features that are not fully understood. Several studies have revealed that the temperature dependence is not in accordance with the Langevin behavior, i.e., the magnetization does not decrease with increasing temperature in the expected way [8][9][10][11][12][13][14][15]. These results have been observed in several synthetic samples, in the iron storage protein ferritin, and in ferrihydrite, which can be found in sediments in nature.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Still, the dependence of the magnetization on particle size and temperature has shown features that are not fully understood. Several studies have revealed that the temperature dependence is not in accordance with the Langevin behavior, i.e., the magnetization does not decrease with increasing temperature in the expected way [8][9][10][11][12][13][14][15]. These results have been observed in several synthetic samples, in the iron storage protein ferritin, and in ferrihydrite, which can be found in sediments in nature.…”
supporting
confidence: 50%
“…1, together with a number of similar experimental observations, give experimental evidence for a temperature dependent magnetic moment that is in accordance with the model for thermoinduced magnetization. Thus the thermoinduced magnetization can explain anomalous magnetic properties of nanoparticles of antiferromagnetic materials, which have been discussed in the literature [4,[8][9][10][11][12][13][14][15].…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Many of these studies were performed to enlighten the possible existence of quantum tunneling in ferritin in the Kelvin range. Less attention has been paid to the magnetic hysteresis, although it was termed "anomalous" in an early report due to the large coercivity (∼1800 Oe at 5 K), irreversibility up to relatively high fields (∼35 kOe), and loop displacement found after field cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Less attention has been paid to the magnetic hysteresis, although it was termed "anomalous" in an early report due to the large coercivity (∼1800 Oe at 5 K), irreversibility up to relatively high fields (∼35 kOe), and loop displacement found after field cooling. 4 Ferritin consists of a hollow spherical shell composed of 24 protein subunits surrounding a ferrihydritelike core. The diameter of the cavity is of the order of 7-8 nm and the average size of the core of horse spleen ferritin is 5 nm.…”
Section: Introductionmentioning
confidence: 99%